EVALUATION OF THE EFFECTIVENESS OF COLLABORATIVE LEARNING DESIGN IN IMPROVING THE STUDENTS' CRITICAL THINKING ABILITY IN WEST SULAWESI UNIVERSITIES - Usri, Usri; Ikbal Salam, Andi Muhammad (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
This study aims to evaluate the effectiveness of collaborative learning design in improving students' critical thinking skills in universities in West Sulawesi. This investigation implements a mixed-methods approach, which entails the acquisition of quantitative data via pre-and post-tests and qualitative data via interviews and observations. This study was conducted for two months, namely August to September 2024, involving 60 students as samples. The results showed a significant increase in students' critical thinking skills, with a higher average post-test score compared to the pre-test. Qualitative data indicated that students engaged in collaborative learning exhibited more significant activity in discussing and enhancing their critical thinking skills. However, some students still faced challenges in applying critical thinking to more complex contexts. Based on these findings, collaborative learning is efficacious in improving students' critical thinking skills, but more attention is needed on classroom management and lecturer facilitation.